Analyses of erythropoiesis from embryonic stem cell‐CD34+ and cord blood‐CD34+ cells reveal mechanisms for defective expansion and enucleation of embryomic stem cell‐erythroid cells. Issue 8 (5th March 2022) - Wang, Shihui; Zhao, Huizhi; Zhang, Huan; Gao, Chengjie; Guo, Xinhua; Chen, Lixiang; Lobo, Cheryl; Yazdanbakhsh, Karina; Zhang, Shijie; An, Xiuli
Abstract: Red blood cells (RBCs) generated ex vivo have the potential to be used for transfusion. Human embryonic stem cells (ES) and induced pluripotent stem cells (iPS) possess unlimited self‐renewal capacity and are the preferred cell sources to be used for ex vivo RBC generation. However, their applications are hindered by the facts that the expansion of ES/iPS‐derived erythroid cells is limited and the enucleation of ES/iPS‐derived erythroblasts is low compared to that derived from cord blood (CB) or peripheral blood (PB). To address this, we sought to investigate the underlying mechanisms by comparing the in vitro erythropoiesis profiles of CB CD34 + and ES CD34 + cells. We found that the limited expansion of ES CD34 + cell‐derived erythroid cells was associated with defective cell cycle of erythroid progenitors. In exploring the cellular and molecular mechanisms for the impaired enucleation of ES CD34 + cell‐derived orthochromatic erythroblasts (ES‐ortho), we found the chromatin of ES‐ortho was less condensed than that of CB CD34 + cell‐derived orthochromatic erythroblasts (CB‐ortho). At the molecular level, both RNA‐seq and ATAC‐seq analyses revealed that pathways involved in chromatin modification were down‐regulated in ES‐ortho. Additionally, the expression levels of molecules known to play important role in chromatin condensation or/and enucleation were significantly lower in ES‐ortho compared to that in CB‐ortho. Together, our findings have uncovered mechanisms for the limited expansion and impaired enucleation of ES CD34 + cell‐derived erythroid cells and may help to improve ex vivo RBC production from stem cells.